Eligibility of the Concepts Used in the Social Studies Curriculum for the Students’ Grade Level in 6th and 7th Grade in Primary School - Öner, Ümmühan; Budak, Fatma Mazman (Tokat Gaziosmanpaşa Üniversitesi, 2012)
The aim of the research is to determine the suitability for student level of some concepts in the Social Studies Program for the 6th and 7th grade. Research was conducted at three selected primary schools in the provinces of Tokat and Elazig in 2008-2009 academic year in fall semester. In this study, descriptive analysis method of qualitative research methods was used, and the answers from the results of the interview were categorized. Percentages (%) and frequencies (f) of the results were developed as a table to determine levels of understanding of concepts. As a result, it can be said that students surveyed have high level of understanding of the concepts, but they have the limited level of understanding and misconceptions in general such as "climate, weather event, geographic location, views, individual" concepts. In addition, it was observed that some students had difficulty in expressing the concepts and the students just tried to explain most concepts with examples

Çalışmanın amacı, ilköğretim 6. ve 7. sınıf Sosyal Bilgiler Programı’nda yer alan bazı kavramların öğrenci düzeyine uygunluğunu belirlemektir. Araştırma 2008–2009 eğitim-öğretim yılının güz döneminde Tokat ve Elazığ illerinde belirlenen üç ilköğretim okulunda yürütülmüştür. Çalışmada nitel araştırma metotlarından betimsel analiz yöntemi kullanılmış ve mülakat sonucunda alınan cevaplar kategorileştirilmiştir. Elde edilen sonuçların yüzde (%) ve frekansları (f) tablo haline getirilerek kavramları anlama düzeyleri belirlenmeye çalışılmıştır. Araştırma sonucunda, öğrencilerin genelde araştırılan kavramları anlama düzeylerinin yüksek olduğu ancak “iklim, hava olayı, coğrafi konum, görüş, birey” gibi bazı kavramlarda sınırlı anlama düzeyinde oldukları ve kavram yanılgısı yaşadıkları söylenebilir. Ayrıca çalışmada, bazı öğrencilerin kavramları ifade etmede zorluk çektiği ve çoğu kavramı sadece örneklerle açıklamaya çalıştıkları görülmüştür
İlköğretim 6. ve 7. Sınıf Sosyal Bilgiler Programlarında Kullanılan Kavramların Öğrenci Düzeyine Uygunluğu